1999
DOI: 10.1152/jn.1999.82.1.290
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of a Restricted Region in the Midline Cerebellar White Matter Evokes Coordinated Quadrupedal Locomotion in the Decerebrate Cat

Abstract: In the reflexively standing acute decerebrate cat, we have previously shown that pulse train microstimulation of the hook bundle of Russel in the midline of the cerebellar white matter, through which crossed fastigiofugal fibers decussate, augments the postural tone of neck, trunk, fore-, and hindlimb extensor muscles. In the present study we examined the possible role of such stimulation in evoking locomotion as the animal is supported by a rubber hammock with its feet contacting the moving surface of a tread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 49 publications
3
78
0
Order By: Relevance
“…Importantly, most of these animals did not recover weightbearing locomotion, as measured by the BBB (Fig. 1 B), which is believed to require supraspinal control (Grillner and Dubuc, 1988;Mori et al, 1999). In contrast, the 12.5 mm SCI group recovered coordinated weight-bearing locomotion (Fig.…”
Section: Relationship Between Recovery Of Lut Function and Hindlimb Fmentioning
confidence: 92%
See 1 more Smart Citation
“…Importantly, most of these animals did not recover weightbearing locomotion, as measured by the BBB (Fig. 1 B), which is believed to require supraspinal control (Grillner and Dubuc, 1988;Mori et al, 1999). In contrast, the 12.5 mm SCI group recovered coordinated weight-bearing locomotion (Fig.…”
Section: Relationship Between Recovery Of Lut Function and Hindlimb Fmentioning
confidence: 92%
“…1 B, BBB) showed significant differences between the 12.5 mm group, which attained weight-bearing locomotion, and the 25 and 50 mm groups, which on average did not. This is an important distinction, because voluntary overground locomotion with full weight support requires supraspinal control (Grillner and Dubuc, 1988;Mori et al, 1999).…”
Section: Severity Of Spinal Cord Injurymentioning
confidence: 99%
“…Indeed, in primate, the spino-mesencephalic tractus and part of the spinoreticular tractus were found to reach different sites in the brainstem, including the caudal mesencephalon (Wiberg et al, 1987;Yezierski, 1988;Craig, 1995). Another origin of this passive response could be related to the close proximity with the SCP (Hazrati and Parent, 1992), which conveys information from the deep cerebellar nuclei, which is considered to be another locomotor center (Mori et al, 1999). The SCP also contains the ventral spino-cerebellar tractus thought to convey information about premotoneuronal activity in the cord.…”
Section: Functional Implication For Locomotionmentioning
confidence: 99%
“…That is, each compartment identified in the CN is proposed to be involved in the same function that has been proposed for its corresponding olivocerebellar group. To give an example, different functions such as control of locomotion (Mori et al, 1999), saccade and other eye movements (Ohtsuka and Noda, 1991), and posture and head orientation (Wilden et al, 2002) have been reported in the FN. The subdivisions of the FN into the rostrodorsal aldolase C-negative part (group III-spinal), centrodorsocaudal part (group IIb-collicular), and centrocaudal part (group IIa-vestibular) in the present study may be directly related to the above functions (locomotion, eye movements, and head orientation).…”
Section: Functional Aspects Of the Nuclear Compartmentsmentioning
confidence: 99%